Prolonged grief disorder among asylum seekers in Germany: the influence of losses and residence status - Comtesse, Hannah (Eur J Psychotraumatol, 2019)
Background: Besides the high exposure to traumatic events, many refugees to Europe experienced tremendous interpersonal losses. Objective: The aim of this study was to investigate the rate and potential risk factors of prolonged grief disorder (PGD) in recently fled asylum seekers who lived in collective accommodations in Germany. Method: Three groups of asylum seekers from different countries (N = 99) completed the Traumatic Grief Inventory Self-Report Version (TGI-SR), Posttraumatic Stress Disorder Checklist-5 (PCL-5), and Patient Health Questionnaire depression module (PHQ-9). Individuals in Group 1 were waiting for asylum decisions (n = 29), Group 2 members were in appeal against rejected asylum claims (n = 32), and Group 3 members had been permitted temporary residence status (n = 38). Results: The loss of a loved person was reported by 92% of participants. The criteria for provisional PGD diagnosis according to Prigerson criteria were met by 20% of participants, 16% fulfilled the criteria for DSM-5 persistent complex bereavement disorder. Probable posttraumatic stress disorder (45%) and depression (42%) rates were high. The total number of lost nuclear family members and PTSD symptoms were associated with higher and temporary residence status was predicted lower PGD symptom levels. Conclusions: These results show that a substantial proportion of asylum seekers suffer from PGD. This points to the need to screen for problematic grief in the current refugee population in Europe.